Case Study Of Omnichannel Marketing in PT Arwana Citramulia Tbk - Amirullah, Taufik; Aruan, Daniel Tumpal H. (Institut Teknologi Sepuluh Nopember, 2019)
Omnichannel marketing is a marketing method that integrates marketing channels to target specific target markets. This research is a case study of the use of omnichannel marketing for B2B activities at PT Arwana Citramulia Tbk, the largest company of many companies in the ceramics industry in Indonesia. PT Arwana Citramulia Tbk targets the middle to lower market segments throughout Indonesia. To be able to dissect how PT Arwana Citramulia Tbk manages its channel, this research will use qualitative methods by conducting unstructured interviews with various stakeholders in PT Arwana Citramulia Tbk. In addition, technology acceptance models are also used to measure revenue from the distribution chain line of PT Arwana Citramulia Tbk, which conducts B2B marketing activities towards the use of online channels to support the use of omnichannel marketing. The technology acceptance model will be used to analyze quantitatively, which is also equipped with results of unstructured interviews regarding the implementation and management of omnichannel marketing by PT Arwana Citramulia Tbk. This research shows that the integration between channels used by PT Arwana Citramulia Tbk is inseparable from the existence of vision, mission, strategy and adequate resources from the top management level to the frontliners